Oxford international lower secondary English student book 1 for grade 6 - Barber, Alison (Karachi : Oxford university press, 2023)
"Oxford International Lower Secondary English Student Book 1" is an engaging and comprehensive textbook designed for Grade 6 students. It aims to develop key English language skills, including reading, writing, speaking, listening, and grammar. The book follows an international curriculum and is structured to promote a strong foundation in English through a variety of interesting and interactive content.
Keywords: English : Textbook; Oxford : Grade 6